2018
DOI: 10.1073/pnas.1714225115
|View full text |Cite
|
Sign up to set email alerts
|

Modular origins of biological electron transfer chains

Abstract: Oxidoreductases catalyze electron transfer reactions that ultimately provide the energy for life. A limited set of ancestral protein-metal modules are presumably the building blocks that evolved into this diverse protein family. However, the identity of these modules and their path to modern oxidoreductases is unknown. Using a comparative structural analysis approach, we identify a set of fundamental electron transfer modules that have evolved to form the extant oxidoreductases. Using transition metal-containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 49 publications
1
50
0
Order By: Relevance
“…One avenue to unraveling this question may be to examine the PEC "fossil record" from a structural perspective. A recent study using the structural database to study oxidoreductase evolution observed a modular origin of biological ET chains (Raanan et al, 2018). An additional way to elucidate this question is to use protein design to test ideas about ancestral PECs that are no longer observed in nature (Mutter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…One avenue to unraveling this question may be to examine the PEC "fossil record" from a structural perspective. A recent study using the structural database to study oxidoreductase evolution observed a modular origin of biological ET chains (Raanan et al, 2018). An additional way to elucidate this question is to use protein design to test ideas about ancestral PECs that are no longer observed in nature (Mutter et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Shuttling of electrons between life's macro-elements has had an evolutionary history at least as long as life itself, culminating in the tightly linked global metabolic network seen today. The genes encoding the enzymes responsible for oxidation and reduction reactions evolved, duplicated and mutated, and have been shared across many branches on the canonical tree of life (David and Alm, 2011;Raanan et al, 2018). An overarching driver for the evolution of life's electron transfer machinery has been the progressive oxidation, both abiotic and biological, of Earth's oceans and atmosphere (Catling et al, 2001;Jelen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Identifying Oxidoreductase Modules. To identify the building blocks of oxidoreductases, we applied a comparative structural alignment approach described previously (10) to a larger dataset of proteins encompassing both metal-containing and organic redox cofactors. Briefly, we isolated local cofactor-binding protein motifs (microenvironments) from deposited high-resolution structures from the Protein Data Bank (PDB) at http://wwpdb.org (13).…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we published a network analysis of over 30,000 metal-coordination sites in high-resolution protein structures and discovered a small number of metal-binding modules that were recurrent across many proteins (10). Modules that bound transition metals often occurred in pairs or larger chains, making paths for electron transfer through the protein matrix.…”
Section: Rossmann Foldmentioning
confidence: 99%